2022
DOI: 10.1155/2022/3172099
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Prognosis-Related Necroptosis Genes for Prognostic Prediction in Hepatocellular Carcinoma

Abstract: Background. The prediction of hepatocellular carcinoma (HCC) survival is challenging because of its rapid progression. In recent years, necroptosis was found to be involved in the progression of multiple cancer types. However, the role of necroptosis in HCC remains unclear. Methods. Clinicopathological parameters and transcriptomic data of 370 HCC patients were obtained from TCGA-LIHC dataset. Prognosis-related necroptosis genes (PRNGs) were identified and utilized to construct a LASSO risk model. The GEO coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In our study, FLT3 showed a strong positive correlation in autophagy, apoptosis, angiogenesis, and epithelial-mesenchymal transition-related scores. Previous studies have been shown that FLT3 was involved in the interaction of focal death, apoptosis and necrotic apoptosis in HCC [30]. FLT3 has the strongest positive correlation with the autophagy related gene PRKCB.…”
Section: Discussionmentioning
confidence: 87%
“…In our study, FLT3 showed a strong positive correlation in autophagy, apoptosis, angiogenesis, and epithelial-mesenchymal transition-related scores. Previous studies have been shown that FLT3 was involved in the interaction of focal death, apoptosis and necrotic apoptosis in HCC [30]. FLT3 has the strongest positive correlation with the autophagy related gene PRKCB.…”
Section: Discussionmentioning
confidence: 87%
“…Many population‐based studies have found AS as a risk factor for Parkinson's disease, with a significantly higher prevalence of Alzheimer's among AS patients, 61,62 which agrees with the GSEA analysis findings in the current study. Moreover, recent studies identified that TARDBP would be a novel NRG in the tumour microenvironment 63,64 . However, studies correlating TARDBP with AS are rare, and the role of TARDBP in AS requires further experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies identified that TARDBP would be a novel NRG in the tumour microenvironment. 63,64 However, studies correlating TARDBP with AS are rare, and the role of TARDBP in AS requires further experimental studies.…”
Section: Prediction Of Hub Gene-targeted Drugs and Construction Of Ce...mentioning
confidence: 99%
“…This resulted in 46 genes with prognostic significance, which were used for further analysis. A common method for constructing models in previous studies was the Lasso method (19,20). In previous studies, the Lasso method was commonly used to construct models, but we found that this may not be the best approach for our data (21).…”
Section: Model Construction By Machine Learningmentioning
confidence: 95%